Efficient One‐Pot Syntheses of 7‐Alkyl‐6H, 7H‐naphtho[1, 2:5, 6]pyrano‐[3, 2‐c]chromen‐6‐ones by 1‐Methyl‐3‐(2‐(sulfooxy)ethyl)‐1H‐imidazol‐3‐ium Chloride. (17th March 2014) - Wan, Yu; Wang, Chao; Wang, Hai‐ying; Zhao, Ling‐ling; Zhang, Xiao‐xiao; Shi, Jing‐jing; Huang, Shu‐ying; Liu, Gui‐Xiang; Wu, Hui
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>